Developing a lecturers’ online for lecturers in UiTM Section 17 Campus / Azlianor Abdul Aziz - Abdul Aziz, Azlianor (2000)
There is another latest technology that can we adapt to make our life easier, which is online education with help of Internet. Therefore, this project entitled Lecturers’ Online serves the same purpose as online education, which involve communication between lecturers and students. The objectives of the proposed project are to ensure that students can get updated information and easy to communicate with their lecturer. The lecturers can distribute the notes and assignments or make some announcement for their students. This project used of several applications such as database management system, HTML with JavaScript and VBScript and electronic form processing for forum or discussion and announcement. Lecturers’ Online working in 24 hours a day. Lecturers’ Online is created especially for UiTM Campus Section 17 lecturers with their students, which contains features of lecturer’s profile, announcement, forum or discussion, notes and assignments.